Mind Mapping: An Effective Learning Technique - Saxena, Bindu (THE PRIMARY TEACHER, 2019)
One of the fundamental principles of National Education Policy is an emphasis on conceptual understanding rather than rote learning and learning-for-exams. To develop the understanding of concepts among the learners, teachers have to use various strategies and techniques in the classroom. These techniques are chosen according to the mental level, needs, and interests of the learner to make the learning process interesting and retain the attention of the learners. It is a fact that children are aware of so many things and the teacher is there to facilitate the learner to construct knowledge and develop concepts. One such technique that is very useful is mind-mapping. In this technique, learners can be involved in the teaching-learning process. It is a very interesting technique and beneficial for the teachers as well as the learners.